Development Of Hollow Fiber Carbon Membranes From Poly (P-Phenylene Oxide) For Gas Separation - Tamar Jaya, Muhammad Azan (2018)
Gas separation based on membrane technology has become more attractive in chemical industry compared to conventional approaches such as cryogenic process and pressure swing adsorption since membrane separations are energy-effective, mechanically simpler system, and can be operated under lower pressures and temperatures. Due to limited chemical resistance and physically unstability of current polymeric membranes, carbon membranes were introduced. However, the current development of carbon membranes have been too focus on novel material development to achieve state-of-the-art separation efficiency. Another important and critical factor is the continuity to further develop the membrane up to commercially valuable which includes the membrane configuration, performance and synthesis optimization and realistic separation tests, unfortunately, appeared very lacking in the literature. This study attempts to fill in the gaps by attempting to continue the development on a hollow fiber carbon membrane synthesized from poly(p-phynylene oxide) (PPO) for H2/N2, O2/N2 and CO2/CH4 gas separations. The PPO membrane (PPOM) was found to be acceptably thermostabilized at optimum temperature of 240°C. The thermostabilized PPOM was then subjected to various pyrolysis conditions, which were pyrolysis temperature, heating rate, and thermal soak time to produce carbon membranes. The carbon membrane performances were determined and optimized based on their single gas permeabilities (H2, N2, O2, CH4, and CO2) and ideal selectivities (H2/N2, O2/N2, and CO2/CH4) with Robeson’s 2008 upperbounds as references. The permeabilities and ideal selectivity changed significantly when different pyrolysis temperatures was applied. Based on the order of kinetic diameter of the gases, the transport of the inert gases through the carbon membrane pyrolyzed at 600 °C were dominated by molecular sieving mechanism and the presence of CO2 surface diffusion was detected through the carbon membrane pyrolyzed at 500 and 700 °C. This properties are directly related to microporous pore structure. Increasing the heating rate increased the permeabilities of the gases and O2/N2 ideal selectivity, while decreased the H2/N2 and CO2/CH4 ideal selectivities. Increasing the thermal soak time slightly increased the H2 and CO2 permeabilities and H2/N2 and CO2/CH4 ideal selectivities. However, it decreased the O2 permeability and O2/N2 ideal selectivity indicating that every separation has different preference of membrane structure which was changed through different pyrolysis formulation. Through the optimization using one-factor-at-time and Robeson’s 2008 upperbound, the performances of H2-H2/N2, O2-O2/N2 and CO2-CO2/CH4 were respectively found to be optimized at 1 °C/min (4 hours), 4 °C/min (0 hours) and 1 °C/min (4 hours). These optimized samples gave averaged H2, O2 and CO2 permeabilities of 2868, 222 and 1205 Barrer, respectively with corresponding H2/N2, O2/N2, and CO2/CH4 ideal selectivities of 586, 40 and 195, respectively. The improvement on the carbon membranes after the optimization were recorded as 80, 9 and 43 times of increment for H2, CO2 and O2 permeabilities and 13, 1.3 and 7 times of increment for H2/N2, CO2/CH4 and O2/N2 ideal selectivities, respectively. The H2 permeability (268 Barrer) and H2/N2 permselectivity (13) from binary gas test were lower than their single H2 permeability and H2/N2 ideal selectivity due to high resistance by N2 and concentration polarization. The O2/N2 permselectivity (13) was 70% lower than the O2/N2 ideal selectivity due to competitive gas transport and concentration polarization. The O2 permeability (243 Barrer) from binary gas test was almost equal to its O2 single permeability. The CO2 permeability (1320 Barrer) and CO2/CH4 permselectivity from binary gas test were almost equal to their CO2 permeability and CO2/CH4 ideal selectivity obtained from the single gas test due to strong CO2 affinity towards the carbon membrane pore walls and pore blocking effect. The purities and recoveries of the H2, O2 and CO2 were 94% and 9%, 57% and 24%, and 96% and 8%, respectively. This study has shown that, the carbon membrane has been successfully synthesized and studied. The optimization implemented has successfully multiplied the carbon membrane separation performance without the need of complicated modifications or additional materials. The realistic separation performance verified that the carbon membrane can indeed deliver high separation efficiency for O2/N2 and CO2/CH4 based on ideal separation characteristics but very poorly for H2/N2.